2005
DOI: 10.1088/0960-1317/15/10/002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of electromechanical coupling for a thin-film PZT membrane: I. Modeling

Abstract: In this two-part paper, the optimization of the electromechanical coupling coefficient for thin-film piezoelectric devices is investigated both analytically and experimentally. The electromechanical coupling coefficient is crucial to the performance of piezoelectric energy conversion devices. A membrane-type geometry is chosen for the study. In part I a one-dimensional model is developed for a membrane composed of two layers, a passive elastic material and a piezoelectric material. The lumped-parameter model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 34 publications
2
63
0
1
Order By: Relevance
“…It is shown that the efficiency depends on the normalized resistance r, the frequency ratio and, in particular, the relative magnitudes of the electromechanical coupling coefficient k 2 e and the mechanical damping ratio ζ m . In general, high energy conversion efficiency can be achieved with large k 2 e ζm ; the improvement of the coupling coefficient k 2 e for micromachined piezoelectric membrane harvesters has been recently investigated by Cho et al [35,36]. The induced damping added to the system due to the removal of mechanical energy from the vibrating structure is obtained based on the derived formula of conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the efficiency depends on the normalized resistance r, the frequency ratio and, in particular, the relative magnitudes of the electromechanical coupling coefficient k 2 e and the mechanical damping ratio ζ m . In general, high energy conversion efficiency can be achieved with large k 2 e ζm ; the improvement of the coupling coefficient k 2 e for micromachined piezoelectric membrane harvesters has been recently investigated by Cho et al [35,36]. The induced damping added to the system due to the removal of mechanical energy from the vibrating structure is obtained based on the derived formula of conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the conversion efficiency can be improved with a larger coupling coefficient and smaller damping. Recently, Cho et al [35,36] performed a series of experiments and proposed a set of design guidelines for the performance optimization of micromachined piezoelectric membrane generators by enhancing the electromechanical coupling coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Some work has begun to address the analytical model gap by focusing on the development of plate theory based electromechanical models [1], [3], [13], [22]- [28]. In [3], [22], explicit analytical equations for effective electromechanical coupling k 2 ef f are defined based on material constants and geometric parameters enabling optimized design for high k 2 ef f .…”
Section: Introductionmentioning
confidence: 99%
“…In [3], [22], explicit analytical equations for effective electromechanical coupling k 2 ef f are defined based on material constants and geometric parameters enabling optimized design for high k 2 ef f . More comprehensive approaches [1], [13], [23]- [27] expand model capabilities to include definitions of lumped mechanical and electrical impedance parameters of the Mason equivalent circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The interdigitated electrode, IDE, configuration presented by Jeon et al at [66] and Park et al at [87] enables to employ the 33 mode and discards the bottom electrode layer, Figure 30. Therefore, the electrode lengths and shapes are important parameters that affect the output voltage due to the non uniformity of the strain along the beam [88]. Kim et al have fabricated and compared piezoelectric energy harvesters based on d 31 and d 33 modes [89].…”
Section: Piezoelectric Energy Harverstersmentioning
confidence: 99%